Chromosomal differentiation of Solanum vespertilio and S. lidii (Solanaceae), rare, endemic species of the Canary Islands (Spain) - Chiarini, Franco Ezequiel (2006)
Amorphometric karyotype analysis was performed on the two Solanum subgenus Leptostemonum species of the Canary Islands (S. lidii and S. vespertilio) to understand patterns of chromosome differentiation, taxonomic relationships and evolutionary implications. The somatic chromosome number, 2n = 24, was documented for both species, supporting the basic chromosome number of Solanum (x = 12). For S. vespertilio, our data confirm a previous report based on meiotic counts, while the chromosome number of S. lidii is reported for the first time. Chromosomes are very small: for S. vespertilio the average chromosome length was 1.5 ± 0.3 μm and the haploid karyotype length 18.4 ± 3.6 μm, and for S. lidii 1.3 ± 0.09 μm and 15.85 ± 1.0 μm, respectively. These sizes are among the smallest for Solanum. Both species have symmetrical karyotypes with the same formula: 8 m pairs + 4 sm pairs. However, in addition to the length differences between the species, the only chromosome pair with a satellite on the short arm is different: it is found on chromosome pair #2 in S. lidii and on a slightly shorter chromosome, pair # 4, in S. vespertilio. Satellites were visualized in almost 100% of the cells of both species. Our karyotype data thus imply that these island species are closely related, and likely evolved in situ on the islands, via sympatric or sequential speciation (S. vespertilioi is the more likely most derived member of the pair). In addition, although both species show a number of derived reproductive traits, like heterandry, zygomorphy, and andromonoecy, they retain the presumptively more generalized symmetrical karyotypes